Development of an Immunochromatographic Assay Kit Using Fluorescent Silica Nanoparticles for Rapid Diagnosis of Acanthamoeba Keratitis - Toriyama, Koji (J Clin Microbiol, 2014)
We developed an immunochromatographic assay kit that uses fluorescent silica nanoparticles bound to anti-Acanthamoeba antibodies (fluorescent immunochromatographic assay [FICGA]) and evaluated its efficacy for the detection of Acanthamoeba and diagnosis of Acanthamoeba keratitis (AK). The sensitivity of the FICGA kit was evaluated using samples of Acanthamoeba trophozoites and cysts diluted to various concentrations. A conventional immunochromatographic assay kit with latex labels (LICGA) was also evaluated to determine its sensitivity in detecting Acanthamoeba trophozoites. To check for cross-reactivity, the FICGA was performed by using samples of other common causative pathogens of infectious keratitis, such as Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, and Candida albicans. Corneal scrapings from patients with suspected AK were tested with the FICGA kit to detect the presence of Acanthamoeba, and the results were compared with those of real-time PCR. The FICGA kit detected organisms at concentrations as low as 5 trophozoites or 40 cysts per sample. There were no cross-reactivities with other pathogens. The FICGA was approximately 20 times more sensitive than the LICGA for the detection of Acanthamoeba trophozoites. The FICGA kit yielded positive results for all 10 patients, which corresponded well with the real-time PCR results. The FICGA kit demonstrated high sensitivity for the detection of Acanthamoeba and may be useful for the diagnosis of AK.